Disciplina e autonomia : um diálogo entre Kant e Adorno - Inácio, Maria de Lourdes Secorun (2012)
The work presented aims to investigate the importance of Education in the process of achieving self-determination adopting, as reference, Theodor Adorno s premises. Since the author aforementioned starts his works from the ideas of Kant, it is mandatory to comprehend Kant s thoughts on enlightenment and educational adulthood. Inspired by these two authors, the main goal of this work is to establish a relationship between the teaching process and the learning ability, which begins since birth and goes until adulthood, approaching how selfdetermination is acquired during this process. Its through education that the human being learns how to live in a society, and only in a democratic society, where there s legitimate authority and not an authoritarian one, it is possible to form sensible and responsible human beings so they can respect one another and not allow that the barbaric acts that once ravaged the world happen once again. To comprehend enlightenment and adulthood in the ideas of these two authors the studies focused on Uber Padagogik by Kant and Erziechun zur Mundgkeit by Adorno, because these are fundamental to investigate the subject in hand. The utilized working method is primarily bibliographical, which implicates in an analyticreconstructive research by choosing and analyzing different fragments from many sources. As a provisory result, it is possible to assert how much Adorno s emancipation is due to Kant s educational adulthood notion, specially regarding the higher demand for the individual to have the courage to think for himself imposed by Kant s enlightenment (Sapere Aude!)